RISK FACTORS FOR TUBERCULOSIS IN BOGOR REGENCY - Tuniroh (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
Tuberculosis, or Pulmonary TB, is dangerous if not managed correctly and appropriately. Bogor Regency is one of the regencies in West Java Province with the highest incidence of TB. This study aims to determine the risk factors for TB events in Bogor Regency. This research method is descriptive-analytic with a cross-sectional approach. The sample of this study is the community who went to the public health center in Bogor Regency, as many as 25 TB sufferers. Data were collected using interviews and observations. Then it is quantitatively analyzed. Results: The results showed that 60% of respondents were > 40 years old, 68% were women, 40% were unemployed, and 68% had low family incomes. Similarly, 56% were exposed to cigarette smoke ith environmental factors, and 68% had a family history of TB. While for the home environment, all indicators show substandard values with a 52-68% percentage. 56-64 % of respondents' knowledge and attitude are not good. Conclusion: from the results of the study, I found that the risk factors for TB in Bogor regency are young age, female gender, not working, low income, a dense living environment and home conditions that are not up to standard, close contact of TB patients in their families and have knowledge and attitudes towards TB prevention that are not good. The need to pay attention to TB risk factors to reduce TB cases in Bogor Regency.